Variational Methods 2016
DOI: 10.1515/9783110430394-002
|View full text |Cite
|
Sign up to set email alerts
|

2. Optimizing spatial and tonal data for PDE-based inpainting

Abstract: Some recent methods for lossy signal and image compression store only a few selected pixels and fill in the missing structures by inpainting with a partial differential equation (PDE). Suitable operators include the Laplacian, the biharmonic operator, and edge-enhancing anisotropic diffusion (EED). The quality of such approaches depends substantially on the selection of the data that is kept. Optimising this data in the domain and codomain gives rise to challenging mathematical problems that shall be addressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 120 publications
(208 reference statements)
0
45
0
Order By: Relevance
“…Instead of quantizing the original pixel values, R-EED chooses the optimal value at each mask position from the quantized co-domain. While this introduces an error to the sparse set K of known data, it has been shown that such brightness optimization can greatly improve the inpainting quality on the inpainting domain Ω \ K [29]. For further technical details of the original R-EED codec, we refer to [3].…”
Section: From Colorization To Compression a Review: Compressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of quantizing the original pixel values, R-EED chooses the optimal value at each mask position from the quantized co-domain. While this introduces an error to the sparse set K of known data, it has been shown that such brightness optimization can greatly improve the inpainting quality on the inpainting domain Ω \ K [29]. For further technical details of the original R-EED codec, we refer to [3].…”
Section: From Colorization To Compression a Review: Compressionmentioning
confidence: 99%
“…So far, there are no dedicated color codecs, but there is a variety of other specialized compression methods, for example for cartoons [24], depth maps [25]- [27], 3-D data [3], or texture [28]. For a full review of diffusion-based compression, we refer to the in-depth survey of Hoeltgen et al [29].…”
Section: Introductionmentioning
confidence: 99%
“…For the defective area in the image, starting from the edge of the target area, using the structure of the non-target area and texture information, the unknown area is predicted and patched according to the matching criteria, so that the filled image is visually reasonable and real [6]. According to different principles, digital image inpainting algorithms can be divided into two categories: structural propagation methods based on partial differential equations (PDEs) [7] and texture synthesis methods based on sample block [8].…”
Section: Introductionmentioning
confidence: 99%
“…The confidence of the pixels in the repaired area is mainly updated, and then the next pixel is prepared for inpainting. Steps (2)(3)(4)(5)(6)(7)(8) are repeated until the face image is repaired. 9.…”
mentioning
confidence: 99%
“…Further applications include the works of Bloor and Wilson (1989) [5], who studied partial differential equations for generating blend surfaces. Finally, refer to [23,45] for a broad overview on PDE-based inpainting and the closely related problem of PDE-based image compression.…”
mentioning
confidence: 99%